Mangrove Ecotourism in Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency, North Sumatra Province (Study on Sustainable Utilization of Coastal Natural Resources) - Harahap, R. Hamdani; Absah, Yeni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This paper aims to analyze mangrove ecotourism in Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency as a manifestation of the utilization of coastal and marine natural resources in terms of social, economic, and cultural institutions. This research was conducted with a qualitative approach, in Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency. Data collection techniques with in-depth interviews, and FGD. Data analysis was carried out by descriptive qualitative. The results showed that the fishing community of Sei Nagalawan Village managed mangrove ecotourism in Kampoeng Nipah by forming a cooperative group called Muara Baimbai. Kampoeng Nipah mangrove tourism management group offers mangrove educational tours, processing mangrove plants into food, such as jeruju crackers, mangrove syrup and mangrove tea. The mangrove eco-tourism management group aims to help the economy of the community, especially fishermen, as well as protect the condition of the coast by planting mangroves in coastal areas. Mangrove Ecotourism in Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency provides an example of sustainable utilization of coastal resources. Keywords: Coastal natural resources, mangrove eco-tourism, sustainability, utilization of coastal natural resources